Factors associated with under Nutrition among Children less than five years in Iganga General Hospital, Iganga District. A Cross-sectional Study. - Agatha Nakimuli (Student's Journal of Health Research, 2022)
Introduction Malnutrition refers to a state of either undernutrition or overnutrition. Undernutrition manifests as wasting or low weight for height (acute malnutrition), stunting or low height for age (chronic malnutrition), underweight or low weight for age, and mineral and vitamin deficiencies or excessiveness. Objectives:  The main objective of the study was to determine the factors associated with undernutrition among children less than five years in Iganga Hospital The specific objectives were to determine the socio-demographic factors such as residence, and age, identify the economic factors such as mother's occupation, and to determine the knowledge of parents/caregivers on factors associated with undernutrition among children less five years in Iganga Hospital in Iganga district Methodology:  A Cross-sectional Study design was used, using both qualitative and quantitative approaches in Iganga General Hospital. The researcher conveniently sampled 100 respondents from 5th January 2022 to 11th January 2022. Data collection was by using self-administered questionnaires which were filled and later analyzed using tables, graphs, and pie charts. Results:  Out of the 100 respondents, the majority; 73(73%) resided in rural areas while 27(27%) resided in urban areas. The majority; 68(68%) knew that diarrheal diseases lead to undernutrition. The majority; 95(95%) knew how to encourage the child to eat while 5(5%) did not know. Majority;80(80%) of the children's mothers' occupation was agricultural work while 9(9%) had formal employment. Conclusion:  The majority (82%) reported that residence influenced the child's nutrition status. The majority (74%) of the participants had average knowledge about undernutrition Recommendation:  Channels of communication like televisions, and radios should be intensely used by health workers with the help of the ministry of health to spread the message about undernutrition, factors associated with it, and nutrition services available so that the incidences of delayed seeking of treatment and severe forms of the disease are reduced.